History of Kirkuk during the British mandate period (Raparin Journal of Humanities (RJH), 2023)
In the late years of World War I (1914-1918), the Ottoman-controlled regions faced a new condition. The city of Kirkuk, as a part of Kurdistan's territory, was not deprived of these new transformations and events.       This research aimed to investigate the history of Kirkuk during the British mandate period. The study found that the arrival of the British in southern Kurdistan, particularly Kirkuk, had a historical background, dating back centuries before the British conquest of the city of Kirkuk in 1918, particularly due to the presence of natural resources in the area. The study also found that Kirkuk residents, as part of Kurdistan's territory, were exhilarated about nationalism after the fall of Ottoman oppression and the arrival of English authorities and that its population had publicly expressed their nationalism desires, for independence and unity with Kurdistan.      The study also reveals that the British have tried in every way to cut off the area from Kurdistan and the Kurdish national movement after the national stance on Kirkuk residents became clear. Kirkuk residents have also broadly supported Sheikh Mahmud and announced him as their leader, and they fully cooperated with him in this regard, which is due to the national sentiment that has developed in the city of Kirkuk.       In the study, we found that in a referendum conducted by the United Nations to resolve the Mosul state issue, residents in Kirkuk mostly agreed to be part of Iraq, even though there were votes demanding independence. Kirkuk people were also generally dissatisfied with the issue of appointing Faisal asking for Iraq, and stood against it, publicly expressing that they would prefer to unite with Kurdistan when Faisal was appointed as crown king to Iraq.